Anti-serum amyloid component P antibodies in patients with systemic lupus erythematosus correlate with disease activity. Issue 12 (13th July 2005) - Zandman-Goddard, G; Blank, M; Langevitz, P; Slutsky, L; Pras, M; Levy, Y; Shovman, O; Witte, T; Doria, A; Rovensky, J; Shoenfeld, Y
Abstract : Objective: To determine the presence of raised titres of anti-serum amyloid P component (SAP) antibodies in patients with systemic lupus erythematosus (SLE) and to evaluate their correlation with clinical disease by the SLEDAI and clinical manifestations. Methods: 452 samples were screened for raised anti-SAP antibody titres by an ELISA. Clinical measures and SLEDAI scores were independently reviewed from medical records. 21 serial samples from 7 patients with SLE were assessed for a change in anti-SAP antibody titres after treatment. Results: Raised anti-SAP antibody titres were detected in 145/328 (44%) SLE samples. In 112 randomly selected samples, 69/112 (62%) patients had raised anti-SAP antibodies and anti-dsDNA antibody titres, whereas only 32/112 (28%) had raised anti-dsDNA antibody titres without raised anti-SAP antibody titres. The mean titre of anti-SAP antibodies in patients with active disease was higher than in patients with inactive disease and controls. SLEDAI scores, assessed in 54 patients, were raised in 26/31 (84%) patients with raised anti-SAP antibody titres. A SLEDAI score ⩾8 was found in 16/31 (52%) patients with raised anti-SAP antibody titres but in only 5/23 (22%) patients without raised titres. No specific pattern of disease was detected in patients with or without raised titres of anti-SAP antibodies. Serial sampling from patients with active SLE and raised anti-SAP antibody titres showed that anti-SAP antibody titres decreased after treatment and correlated with clinical improvement. Conclusion: Raised anti-SAP antibody titres detected in patients with SLE correlate with disease activity and decrease with improvement of clinical disease, and thus may serve as an additional prognostic marker.